2023
DOI: 10.1021/acssuschemeng.3c03611
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Carbon Black-Based Counter Electrodes for Copper (I)/(II)-Mediated Dye-Sensitized Solar Cells

Abstract: Carbon black (CB) is a readily available, inexpensive carbonaceous material with good catalytic activity, which has been utilized alone or in composites to fabricate highly efficient counter electrodes (CEs) for dye-sensitized solar cells (DSSCs) employing copper redox couple. First, the catalytic activities of the CEs with various CB layers were evaluated and the results reveal that the number of CB layers is an important factor determining the electrochemical behaviors of the CEs. At the optimal CB layers, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…Despite these features, Pt is scarce and expensive, making it unfavorable for large-scale commercial manufacturing. Furthermore, Pt is prone to corrosion in iodide-based electrolytes, leading to PtI 4 . , Extensive research to replace Pt as a CE has been conducted on various classes of materials; among these, carbonaceous materials (two-dimensional graphene, carbon black, and CNTs), , transition metal dichalcogenides (MoS 2 , SnS 2 , WSe 2 , and others), carbon–metal composites, , metal oxides (NiO, V 2 O 5 , and MoO 3 ), , and conductive polymer composites , were evaluated. In another approach, CuS/Graphene heterostructured nanocomposites were utilized as CE in DSSC.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these features, Pt is scarce and expensive, making it unfavorable for large-scale commercial manufacturing. Furthermore, Pt is prone to corrosion in iodide-based electrolytes, leading to PtI 4 . , Extensive research to replace Pt as a CE has been conducted on various classes of materials; among these, carbonaceous materials (two-dimensional graphene, carbon black, and CNTs), , transition metal dichalcogenides (MoS 2 , SnS 2 , WSe 2 , and others), carbon–metal composites, , metal oxides (NiO, V 2 O 5 , and MoO 3 ), , and conductive polymer composites , were evaluated. In another approach, CuS/Graphene heterostructured nanocomposites were utilized as CE in DSSC.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29,30 ] Furthermore, the instability of DSSCs originated from the degradation of catalytic activity of the counter electrode (CE) and thermal decomposition and photo‐bleaching of the dye due to the continuous irradiation of sunlight. [ 9 ] Although degradation of catalytic activity of the CE can be overcome by using a stable CE [ 31–33 ] and thermal decomposition and dye photo‐bleaching at indoor light are negligible, electrolyte leakage through surlyn sealing remains a significant issue for commercializing DSSCs. Recently, glass frits have been used to seal DSSCs, and promising stability has been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Furthermore, the instability of DSSCs originated from the degradation of catalytic activity of the counter electrode (CE) and thermal decomposition and photo-bleaching of the dye due to the continuous irradiation of sunlight. [9] Although degradation of catalytic activity of the CE can be overcome by using a stable CE [31][32][33] and thermal decomposition and dye photo-bleaching at indoor light are negligible, DOI: 10.1002/solr.202300942 Dye-sensitized solar cells (DSSCs)-integrated Li-ion batteries (LIBs) are considered a promising solution as a wireless power source for the increasing number of miniaturized portable devices and the internet of things (IoTs). However, DSSCs suffer from stability issues because of the using volatile electrolyte solvents that leak through the seal.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, the seminal work on the well-known dye-sensitized solar cell (DSSC) by Grätzel and O’Regan was initially reported, and since then various research groups have been involved in optimizing the DSSC’s efficiency and its outdoor durability . This includes the development of new photoanodes, , counter electrodes, , dyes, ,, and electrolyte media. Notably, researchers have achieved high-efficiency DSSCs with power conversion efficiency (PCE %) values ranging between 12 and 15% under 1 Sun illumination using different redox mediators such as I – /I 3 – , thiolate/disulfide, cobalt, and copper complexes. Furthermore, recent studies have demonstrated the superior performance of DSSCs operating under ambient light conditions compared to other solar devices. , Remarkably, these devices exhibited high PCEs with various mediators. For instance, using I – /I 3 – mediators, PCEs have surpassed 30% .…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, the seminal work on the well-known dye-sensitized solar cell (DSSC) by Graẗzel and O'Regan was initially reported, 1 and since then various research groups have been involved in optimizing the DSSC's efficiency and its outdoor durability. 2 This includes the development of new photoanodes, 3,4 counter electrodes, 5,6 dyes, 2,7,8 and electrolyte media. 9−11 Notably, researchers have achieved high-efficiency DSSCs with power conversion efficiency (PCE %) values ranging between 12 and 15% under 1 Sun illumination using different redox mediators such as I − /I 3 − , thiolate/disulfide, cobalt, and copper complexes.…”
Section: ■ Introductionmentioning
confidence: 99%